2017
DOI: 10.1016/j.cell.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Control of Mammalian Cortical Neurogenesis by m6A Methylation

Abstract: SUMMARY N6-methyladenosine (m6A), installed by the Mettl3/Mettl14 methyltransferase complex, is the most prevalent internal mRNA modification. Whether m6A regulates mammalian brain development is unknown. Here we show that m6A depletion by Mettl14 knockout in embryonic mouse brains prolongs cell cycle of radial glia cells and extends cortical neurogenesis into postnatal stages. m6A depletion by Mettl3 knockdown also leads to prolonged cell cycle and maintenance of radial glia cells. m6A-sequencing of embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
629
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 627 publications
(678 citation statements)
references
References 66 publications
22
629
2
Order By: Relevance
“…We found that expression of DISC1 765–835 peptide, but not DISC1 L822Q control peptide, caused substantially decreased cell cycle exit (Figure 4B). We next performed fluorescence-activated cell sorting (FACS) analysis with dissociated cortex after in utero electroporation and EdU treatment as described above (Yoon et al, 2017a) (Figure S5C). The FACS analysis revealed that progression from S/G 2 /M to G 0 /G 1 was significantly reduced by the expression of the DISC1 765–835 peptide, but not by the DISC1 L822Q control peptide (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that expression of DISC1 765–835 peptide, but not DISC1 L822Q control peptide, caused substantially decreased cell cycle exit (Figure 4B). We next performed fluorescence-activated cell sorting (FACS) analysis with dissociated cortex after in utero electroporation and EdU treatment as described above (Yoon et al, 2017a) (Figure S5C). The FACS analysis revealed that progression from S/G 2 /M to G 0 /G 1 was significantly reduced by the expression of the DISC1 765–835 peptide, but not by the DISC1 L822Q control peptide (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Five pulses (43 V, 50 ms in duration with a 950 ms interval) were delivered with tweezer electrodes (CUY650–5, Nepa Gene) by a CUY21SC electroporator (Nepa Gene) as previously described (Yoon et al, 2017a; Yoon et al, 2017b). Electroporated organoids were transferred back to Spin 3 bioreactor and cultured until fixation.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-type-specific responses may also result from other mechanisms, such as post-transcriptional modification of RNA, that affect gene expression (and are referred to as ) 100 . Because RNA modifications were proposed to affect activity-induced RNA editing and localization in the brain 101 and are known to affect cortical development 102 , it is likely that RNA modifications have an important role in axon regeneration. Indeed, nerve injury was recently shown to induce an increase in N6-methyladenosine, the most abundant modification of mRNA, in transcripts encoding many RAGs, and deletion of the enzymes responsible for this epitranscriptomic mark was shown to reduce axon regeneration in the PNS 103 .…”
Section: Injury Signallingmentioning
confidence: 99%
“…Considering the rapid cell division of neuroblasts, well-designed neurogenic programs, such as sequential expression of temporal transcription factors (Doe, 2017), might be pre-encoded before the onset of neurogenesis. Future studies are needed to address potential epigenetic and epitranscriptomic pre-patterning mechanisms before cell division (Yoon et al, 2017). Functionally, do four sister T4/T5 neurons derived from the same neuroblast cooperate for motion sensing?…”
mentioning
confidence: 99%